2022
DOI: 10.3390/medicina58091283
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Pacing Affects Left Atrial Morphological and Functional Parameters Early after Pacemaker Implantation

Abstract: Background and Objectives: Chronic atrial stimulation might impair left atrial (LA) function. We aimed to assess the impact of atrial pacing burden on LA volumetric and functional parameters after implantation of a dual-chamber pacemaker. Materials and Methods: The prospective study included 121 subjects with sinus node disease (SND) or atrioventricular block (AVB) that received a dual-chamber pacemaker. After device implantation, the subjects were divided into three groups: (1) SND with a lower rate (LR) set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They noticed a link between higher atrial pacing burden and reduced LA reverse remodeling [ 13 ]. We have previously demonstrated that more atrial pacing was linked to negative LA remodeling and worsened systolic and diastolic LA functions in patients with preserved LV EF receiving dual-chamber pacemakers [ 15 ]. Though the degree to which different pacing modes, interatrial and AV dyssynchrony, RA pacing burden affected LA function remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They noticed a link between higher atrial pacing burden and reduced LA reverse remodeling [ 13 ]. We have previously demonstrated that more atrial pacing was linked to negative LA remodeling and worsened systolic and diastolic LA functions in patients with preserved LV EF receiving dual-chamber pacemakers [ 15 ]. Though the degree to which different pacing modes, interatrial and AV dyssynchrony, RA pacing burden affected LA function remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial pacing by itself can also cause deterioration of LA function. That can result in arrhythmias regardless of reduced or preserved LV systolic function [ 10 , 11 , 12 , 13 , 14 , 15 ]. In a population of patients with reduced LV ejection fraction (LVEF) receiving cardiac resynchronization therapy, higher right atrial (RA) pacing burden can lead to worsening of LA function, higher risk of AF and HF worsening [ 13 ].…”
Section: Introductionmentioning
confidence: 99%